Sugar–Protein Connectivity Impacts on the Immunogenicity of Site-Selective Salmonella O-Antigen Glycoconjugate Vaccines - Stefanetti, Giuseppe (Angew Chem Int Ed Engl, 2015)
A series of glycoconjugates with defined connectivity were synthesized to investigate the impact of coupling Salmonella typhimurium O-antigen to different amino acids of CRM(197) protein carrier. In particular, two novel methods for site-selective glycan conjugation were developed to obtain conjugates with single attachment site on the protein, based on chemical modification of a disulfide bond and pH-controlled transglutaminase-catalyzed modification of lysine, respectively. Importantly, conjugation at the C186-201 bond resulted in significantly higher anti O-antigen bactericidal antibody titers than coupling to K37/39, and in comparable titers to conjugates bearing a larger number of saccharides. This study demonstrates that the conjugation site plays a role in determining the immunogenicity in mice and one single attachment point may be sufficient to induce high levels of bactericidal antibodies.